α(S1)-casein, which is essential for efficient ER-to-Golgi casein transport, is also present in a tightly membrane-associated form - Le Parc, Annabelle (BioMed Central, 2010)
BACKGROUND: Caseins, the main milk proteins, aggregate in the secretory pathway of mammary epithelial cells into large supramolecular structures, casein micelles. The role of individual caseins in this process and the mesostructure of the casein micelle are poorly known. RESULTS: In this study, we investigate primary steps of casein micelle formation in rough endoplasmic reticulum-derived vesicles prepared from rat or goat mammary tissues. The majority of both α(S1)- and β-casein which are cysteine-containing casein was dimeric in the endoplasmic reticulum. Saponin permeabilisation of microsomal membranes in physico-chemical conditions believed to conserve casein interactions demonstrated that rat immature β-casein is weakly aggregated in the endoplasmic reticulum. In striking contrast, a large proportion of immature α(S1)-casein was recovered in permeabilised microsomes when incubated in conservative conditions. Furthermore, a substantial amount of α(S1)-casein remained associated with microsomal or post-ER membranes after saponin permeabilisation in non-conservative conditions or carbonate extraction at pH11, all in the presence of DTT. Finally, we show that protein dimerisation via disulfide bond is involved in the interaction of α(S1)-casein with membranes. CONCLUSIONS: These experiments reveal for the first time the existence of a membrane-associated form of α(S1)-casein in the endoplasmic reticulum and in more distal compartments of the secretory pathway of mammary epithelial cells. Our data suggest that α(S1)-casein, which is required for efficient export of the other caseins from the endoplasmic reticulum, plays a key role in early steps of casein micelle biogenesis and casein transport in the secretory pathway.